Strong-field-induced bond rearrangement in triatomic molecules - Zhao, S.; Jochim, Bethany; Feizollah, Peyman; Rajput, Jyoti; Ziaee, F.; P., Kanaka Raju; Kaderiya, B.; Borne, K.; Malakar, Y.; Berry, Ben; Harrington, J.; Rolles, D.; et al. (My University, 2019)
A comparative study of bond rearrangement is reported for the double ionization of three triatomic molecules: carbon dioxide, carbonyl sulfide, and water (D2O). Specifically, we study the formation of the molecular cation AC+ from the edge atoms of a triatomic molecular dication ABC2+ following double ionization by intense, short (23 fs, 790 nm) laser pulses. The comparison is made using the double ionization branching ratio of each molecule, thereby minimizing differences due to differing ionization rates. The rearrangement branching ratio is highest for water, which has a bent initial geometry, while CO2 and OCS are linear molecules. The angular distribution of O2+ fragments arising from CO2 is essentially isotropic, while SO+ from OCS and D+2 from D2O are aligned with the laser polarization. In the CO2 and D2O cases, the angular distributions of the bond rearrangement channels are different from the angular distributions of the dominant dissociative double ionization channels CO++O+ and OD++D+. Only the angular distribution of SO+ from OCS is both aligned with the laser polarization and similar to the angular distribution of the largest dissociative channel, CO++S+. The mixed behavior observed from the angular distributions of the different molecules stands in contrast to the relative consistency of the magnitude of the bond rearrangement branching ratio.
Keywords: bond rearrangement; triatomic molecules; double ionization